Analisis Kebijakan Pembangunan Olahraga Jawa Barat (Penelitian Dilakukan Pada Bidang Kebudayaan Olahraga) - Aang Solahudin Anwar; Harmawati (LPPM Universitas Buana Perjungan Karawang, 2019)
This research is a qualitative research that aims to find out why sports policy in West Java is able to produce various awards. Seeing the extent of the assessment of sports policy in West Java in the Field of Early Childhood Sports Culture. The author tries to focus on policies in the field of sports acculturation, more specifically sports acculturation policies in the Karawang district. The method used in this study uses a qualitative method by carrying out several approaches to the study of literature, interviews and field studies in the field under study. The purpose of this qualitative research is to know the continuation of sports development after the leadership of the Governor and the head of West Java and the district in particular, and to find out the direction of West Java sports development policies specifically in the field of sports culture in Karawang district and new policies or evaluations of the policies that have been implemented.